Pairwise Locally Compact Space and Pairwise Locally Lindelőf Space - Nabeela I. Abualkishik, Hasan Z. Hdeib (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this paper we deﬁne pairwise locally compact space and pairwise locally lindelöf space and study their properties and their relations with other bitopological spaces. several examples are discussed and many will known theorems are generalized concerning pairwise locally compact space and pairwise locally lindelöf space. and we shall investigate subspaces of pairwise locally compact space and pairwise locally lindelöf space and also bitopological spaces which are related to pairwise locally compact space and pairwise locally lindelöf space.